The preparation of new functionalized [2.2]paracyclophane derivatives with N-containing functional groups - Hopf, Henning; Narayanan, Swaminathan Vijay; Jones, Peter G. (Beilstein Journal of Organic Chemistry, 2015)
The two isomeric bis(isocyanates) 4,12- and 4,16-di-isocyanato[2.2]paracyclophane, 16 and 28, have been prepared from their corresponding diacids by simple routes. The two isomers are versatile intermediates for the preparation of various cyclophanes bearing substituents with nitrogen-containing functional groups, e.g., the pseudo-ortho diamine 8, the bis secondary amine 23, and the crownophanes 18 and 19. Several of these new cyclophane derivatives (18, 19, 22, 26, 28) have been characterized by X-ray structural analysis.
Keywords: azides; crownophanes; cyclophanes; isocyanates; stereochemistry; X-ray analysis